Levantamiento y análisis preliminar de las fuentes primarias y secundarias de la Historia de la Comunicación de la provincia del Azuay en el período 1755-1875. - Torres Rodríguez, Wilman Efrén (2014)
The History of Communication of Ecuador has a substantial importance because it will gradually discover the evolution in different periods the way to communicate between the citizenship. In Cuenca in the year 1821 worked a small lithographic press with types of wood in which was printed collections, letterheads, flyers. While the printing press arrived in Ecuador in 1754, i hope more than half a century for Col. Ignacio Torres bring Basin printing in 1827 and made available to Vincent Solano to publish the first newspaper " The echo of the Azuay" in 1828. Since then were issued several newspapers, flyers, newsletters. Each half was in relation to topics and current events, the editors were generally political as former presidents, governors, military, religious, influential characters in each era. The themes of its editions always contain important issues to deal with, whether debaters, informational, political or critical. A particular feature of all was his short tenure; however the citizenship was being kept informed on the different periods of communication through the media that were appearing.